Transformation towards a Low-Emission and Energy-Efficient Economy Realized in Agriculture through the Increase in Controllability of the Movement of Units Mowing Crops While Simultaneously Discing Their Stubble - Orynycz, Olga; Nadykto, Volodymyr; Kyurchev, Volodymyr; Tucki, Karol; Kulesza, Ewa; Надикто, Володимир Трохимович; Кюрчев, Володимир Миколайович (Basel : MDPI, 2024)
EN: When harvesting cereals and fodder grasses, a two-phase method is often used. This process is carried out using trailed and suspended collecting units. The former are asymmetrical and often pose problems regarding the stability of their movement in the horizontal plane. In practice, suspended harvesting units with a front-mounted header are becoming more and more widely used. The disadvantage of their use is that the soil is exposed after passing through the space between the swaths of the mown crop. This is followed by an intense loss of moisture. In order to eliminate this shortcoming, a collecting unit was proposed, consisting of a tractor with a front attachment and a disc harrow mounted at the rear. An appropriate mathematical model was developed to justify the scheme and parameters of such a unit. In this case, this model is used to assess the controllability of the movement of the dynamic system under the influence of control action in the form of the angular rotation of the tractor’s steered wheels. As a result of mathematical modelling, it was found that satisfactory controllability of the movement of the harvesting units can be ensured by acting on the tractor’s driven wheels with a frequency of 0–1 s−1 and a working speed of close to 3 m·s−1. In this case, it is desirable to set the deflection resistance coefficient of the rear tyres of the tractor (and therefore, the air pressure in them) to a smaller value, and that of the front tyres to a larger value. This helps both to improve the movement controllability of the harvesting unit and to reduce its energy consumption by an average of 6.75%. The emissivity of selected harmful chemicals and particulates emitted by the harvesting unit, depending on the fuel burned, was also examined. The way in which the use of the harvesting unit affects the reduction of emissions of harmful compounds into the atmosphere was also revealed.
Keywords: two-phase harvesting method; energy saving header; disc harrow; amplitude frequency characteristic; phase frequency characteristic; crop plants; двофазний метод збору; енергозберігаючий колектор; дисковий гарроу; характеристика амплітудної частоти; характеристика фазової частоти